Exchange Rate Pass-Through When Market Share Matters - Froot, Kenneth A.; Klemperer, Paul D. (American Economic Review, 1989)
We investigate the pass-through from exchange rates to import prices when firms' future demands depend on current market shares. Foreign firms may either raise or lower their dollar export prices when the dollar appreciates temporarily (i.e., the pass-through may be perverse) and import prices may be more sensitive to expected future than to current exchange rates. We explore whether expected future exchange rates provide a clue to the puzzling recent behavior of U.S. import prices.